Assessment of radioecological capacity of the territories under the impact of nuclear fuel cycle objects - І. P. Drozd; Yu. S. Oliynyk; O. A. Sova (Ядерна фізика та енергетика)
Scientific analysis of the theoretical basis of the methodology for estimating the radioecological capacity of the territories in the zone of the influence of the operating facilities of nuclear fuel cycle in Ukraine was carried out. Existing concept of the environmental security under the technogenic impact to the environment was considered. The methods of the estimation of the radioecological capacity of the territory near existing and new potential enterprises in the context of human security was proposed.